Research on the Method of Predicting Fractional Flow Reserve Based on Multiple Independent Risk Factors - Zhang, Honghui; Li, Gaoyang; Hou, Qianwen; Yang, Yinlong; Wei, Hongge; Yang, Yujia; Qu, Zhuoran; Xie, Jinjie; Qiao, Aike (Frontiers in Physiology, 2021)
Background：Using diameter stenosis (DS) revealed through coronary angiography for predicting fractional flow reserve (FFR) usually results in a high error of the detection results. This paper investigates the prediction method of FFR in patients with coronary stenosis based on multiple independent risk factors so as to improve the prediction accuracy. Methods:Multiple independent risk factors were identified through literature analysis to calculate the corresponding odds ratio. The weight value of each independent risk factor was derived based on the odds ratio by using the improved analytic hierarchy process (IAHP). A method based on the top seven independent risk factors with the higher weight values was proposed to predict the FFR. The proposed method was applied to the prediction of the FFR of 253 patients with coronary stenosis and compared with previous methods (DS alone and a simplified scoring system). Results:In addition to DS, other factors such as the gender, body mass index (BMI), location of stenosis (LS), type of coronary artery distribution (TCAD), left ventricular ejection fraction (LVEF) and left myocardial mass (LVM) are the independent risk factors with higher weight values for predicting FFR. The area under the receiver operating characteristic curve (AUC) of the proposed method is 84.3% (95% CI: 79.2%-89.4%) which is larger than 65.3% (95% CI: 61.5%-69.1%) of DS alone and 74.8% (95% CI: 68.4%-81.2%) of a simplified scoring system. Conclusion:The proposed method based on multiple independent risk factors can effectively improve the prediction accuracy of FFR